Wasiat in the Development of Contemporary Islamic Law in Indonesia - Muntasir; Oyo Sunaryo Mukhlas (al-Afkar, Journal For Islamic Studies, 2024)
Islam brings a set of legal rules, namely shari'a on inheritance, zakat, infaq, shadaqah, grants, waqf and wasiat. Wasiat is the transfer of ownership of something to someone after the owner dies. Wasiat in the Compilation of Islamic Law (KHI) is defined as the giving of an object from the testator to another person or institution that will take effect after the testator dies. With the approach of normative or doctrinal legal studies, it has been concluded that the original will as a gift of a person to another person either in the form of an object, or just a benefit that will belong to the person who will be given a will without expecting a reward (tabarru') whose implementation takes effect after the person who testifies has passed away.   In the development of contemporary Islamic law has been known with the existence of a mandatory will, which is known as Egypt, Syria, Morocco and Tunisia is to address the issue of grandchildren whose parents died before his grandparents. While in Indonesia, the mandatory will is enacted to overcome the relationship between adopted children and adoptive parents who cannot receive inheritance by being given a mandatory will as much as 1/3 of the testamentary property or inheritance property. In the further development of wills wajibah is recontructed to provide parts to non-Muslim heirs, through several court decisions into jurisprudence.